KOMUNIKASI INTERPERSONAL BARISTA SE-NUSA COFFEE SHOP PEKANBARU DALAM MENCIPTAKAN KEPUASAN PELANGGAN - Adhellya, Raysha; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Barista has a very strategic role in the sustainability of a coffee shop. Baristas must have good interpersonal communication skills, because interpersonal communication carried out by baristas has a very significant effect on obtaining and maintaining customer satisfaction. Interpersonal communication is the sending of messages from a person and received by another person or group of people with immediate effects and feedback. In this study, the problem analyzed is how the process, pattern, as well as aspects of openness and empathy, as well as obstacles in the interpersonal communication process between Se-nusa Coffee Shop baristas and customers. The purpose of this research is to analyze and understand the processes, patterns, aspects of openness, aspects of empathy and barriers to interpersonal communication between baristas and customers. This research uses descriptive qualitative research methods. With data collection techniques in the form of interviews, observation, and documentation. As for determining the research subject using Accidental techniques and Survey techniques. Informants in this study amounted to 9 people. While the data analysis technique uses interactive analysis according to Miles and Huberman, namely from data collection, data reduction, data presentation, and conclusion drawing. The technique of checking the validity of this research data is the extension of participation and triangulation. The results of this study found, 1) the communication process between baristas and customers is carried out by verbal communication in the form of spoken and written language, while non-verbal in the form of smiles, views, body movements and clothing worn. 2) the pattern of interpersonal communication between baristas and customers is a circular pattern. 3) Se-nusa Coffee Shop baristas are quite open to the menu served, criticism and suggestions from customers. 4) Se-nusa Coffee Shop baristas provide good empathy to customers. 5) interpersonal communication barriers that occur between baristas and customers are not severe obstacles and can be resolved directly between the two.